AN EVALUATION OF AN ENGLISH LANGUAGE TEACHING EDUCATION PROGRAM IN TERMS OF TEACHER AUTONOMY - Sibel Kahraman (Informascope, 2015)
The present study aims to evaluate an English Language Teaching (ELT) Program of a university in Turkey in terms of teacher autonomy development. It attempts to do so by investigating course catalogues described in the European Credit Transfer and Accumulation System (ECTS) of the program through the framework of European Profile for Language Teacher Education (EPLTE). The paper reports on the research findings from that analysis and the other qualitative analysis using a semi-structured interview conducted with seven teacher educators who have had experience with the ELT program. The results show that the ELT program has covered most of the aspects included in the checklist and the teacher educators shared positive views about the program in terms of autonomy development. They also gave some suggestions about the program and the context of the courses.